2002
DOI: 10.1300/j013v35n01_03
|View full text |Cite
|
Sign up to set email alerts
|

Presenting the Female Condom to Men: A Dyadic Analysis of Effect of the Woman's Approach

Abstract: Although male partner resistance to female condom use has been reported, little is understood about circumstances under which partners will agree to female condom use. This study documents the experiences of couples who have worked together to achieve female condom use. As part of a prospective female condom efficacy study, female participants (age 18-34) received a behavioral intervention and an assortment of take-home items. Selected women and their partners were recruited for a qualitative interview focusin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…Given data suggesting that 100% consistent use of condoms is necessary to realize any benefit in terms of STD protection (Macaluso, Artz, et al, in press), however, we recommend using a 100% condom use goal. We find that some women actually use this commitment as a way of persuading their partners to use condoms (Penman-Aguilar et al, 2002).…”
Section: (Continued)mentioning
confidence: 84%
See 1 more Smart Citation
“…Given data suggesting that 100% consistent use of condoms is necessary to realize any benefit in terms of STD protection (Macaluso, Artz, et al, in press), however, we recommend using a 100% condom use goal. We find that some women actually use this commitment as a way of persuading their partners to use condoms (Penman-Aguilar et al, 2002).…”
Section: (Continued)mentioning
confidence: 84%
“…After this assessment, the nurse clinicians were asked to make sure that every woman understood that this video was to be shown to her partner and was different from the one she had seen. Qualitative interviews with 26 study participants and their male partners suggest that the video made it easier for some women to present the female condom to their partner, persuaded a number of male partners to try the device, and promoted continued use of the female condom (Penman-Aguilar et al, 2002). A longitudinal assessment of the impact of the video on female condom use patterns suggested that women who received the video (a) were less likely to discontinue use of female condoms after a single trial, (b) used more lubricant, and (c) said their partners were less bothered by problems associated with female condoms.…”
Section: Gotta Use the Lubementioning
confidence: 99%
“…It is surprising, therefore, that only a small number of female condom studies to date (e.g., Meekers & Richter, 2005; Penman-Aguilar et al, 2002; Witte et al, 2006) have assessed men’s experiences directly. Men’s perspectives and experiences of female condom use can provide important insights into some of the key factors that impede or facilitate use of the device, particularly in sub-Saharan Africa, which continues to account for the majority of new HIV infections globally (World Health Organization, 2011).…”
Section: Structural and Cultural Factors Affecting Female Condom Usementioning
confidence: 99%
“…A woman's sexual comfort with and enjoyment of this method (influenced by such factors as the polyurethane's enhancement of heat transfer and the potential for increased clitoral stimulation from the condom's outer ring) reportedly contribute to uptake and continuation. 58,59,[61][62][63] Other methods also have been studied for sexual acceptability, albeit less comprehensively. In a longitudinal study of new oral contraceptive users in the United States, researchers found that a decrease in users' libido and sexual enjoyment was strongly associated with discontinuation.…”
Section: Contraceptive Use Patternsmentioning
confidence: 99%